2010
DOI: 10.1177/1527002509359758
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Minor League Baseball Attendance

Abstract: Like Major League Baseball (MLB), minor league baseball attendance may be influenced by the quality of the team. We use a data set encompassing all A, AA, and AAA minor league teams from 1992 to 2006 and find a positive relationship between a minor league team’s winning percentage and attendance. We also find evidence that minor and MLB are substitutes as increased ticket prices for the nearest MLB team lead to higher minor league attendance if that team is within 100 miles. Similarly, we find that during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 11 publications
5
40
1
Order By: Relevance
“…Similarly, economic theory measures firm success through profit maximization which, in sports, has most often been operationalized as attendance demand (see Borland and Macdonald, , for a review). Traditional demand theory models attendance as a function of price, quality (win percent and new stadium), substitutes (MLB teams and stadiums), and income (per capita income) (Gitter and Rhoads, ). Therefore, certain controls are warranted when evaluating our research questions, which focus on how affiliation partner alliances may influence attendance demand for minor league teams.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, economic theory measures firm success through profit maximization which, in sports, has most often been operationalized as attendance demand (see Borland and Macdonald, , for a review). Traditional demand theory models attendance as a function of price, quality (win percent and new stadium), substitutes (MLB teams and stadiums), and income (per capita income) (Gitter and Rhoads, ). Therefore, certain controls are warranted when evaluating our research questions, which focus on how affiliation partner alliances may influence attendance demand for minor league teams.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, certain controls are warranted when evaluating our research questions, which focus on how affiliation partner alliances may influence attendance demand for minor league teams. Although less work has been undertaken on minor league baseball, existing research has shown that significant demand features in one classification (AAA, AA, A, or rookie) may be insignificant in other classifications (Branvold et al ., ; Gitter and Rhoads, ; Roy ). To this extent, we anticipate the potential for different effects between the AAA and AA classifications tested in this study…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While much research has been conducted on the relationship between a variety of factors and sport spectator attendance patterns in the United States, most of this body of work is relevant to the "big three" sports of football, basketball, and baseball (Berri, Schmidt, & Brook, 2004;Burdekin & Idson, 1991;Chupp, Stephenson, & Taylor, 2007;Gitter & Rhodes, 2010;Gitter & Rhodes, 2011;Leadley & Zygmont, 2005;Welki & Zlatoper, 1999). With respect to soccer, the global literature on variables associated with spectator attendance is abundant (Allen & Roy, 2008;Bainbridge, Cameron, & Dawson, 1996;Brandes, Franck, & Nuesch, 2008, Feddersen & Maenning, 2009Garcia & Rodríguez, 2002;González-Gómez & Picazo-Tadeo, 2010;Madalozzo & Villar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A MiLB season ticket holder or multiple-game ticket buyer who is found to have low fan identification is more of a risk to discontinue or decrease his or her investment in the team. Gifis and Sommers (2006) and Gitter and Rhoads (2010) found MiLB fans have an interest in baseball's roots which helps with attendance. MiLB attendance often surges when fireworks and other promotions are added (Paul & Weinbach, 2013).…”
Section: Study Significancementioning
confidence: 99%